1977
DOI: 10.1002/ijc.2910200504
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma: Significance of changes in epstein‐barr virus‐related antibody patterns following therapy

Abstract: Sera were collected a t intervals of 3 t o 8 months over a 4-t o 5-year period from more than 103 patients with nasopharyngeal carcinomas (NPC) and examined for their spectra and titers of antibodies t o Epstein-Barr virus (EBV)-related antigens. They were titrated for IgG, IgA and I g M antibodies t o EB viral capsid antigen (VCA), for IgG and IgA antibodies t o the D (diffuse) and R (restricted) components of the EBV-determined early antigen (EA) complex, and for antibodies t o the EBVassociated nuclear anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2
3

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(72 citation statements)
references
References 21 publications
3
64
2
3
Order By: Relevance
“…In several prognosis studies, the anti-EBVs declined significantly after nasopharyngeal carcinoma treatment and elevated again when nasopharyngeal carcinoma relapsed (5)(6)(7)(8). In our previous report from this cohort study, the hazard ratios associated seropositivity of anti -EBV viral capsid antigen immunoglobulin A and anti -EBV DNase were higher for the nasopharyngeal carcinoma developed <5 years than that developed z5 years after recruitment (13).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In several prognosis studies, the anti-EBVs declined significantly after nasopharyngeal carcinoma treatment and elevated again when nasopharyngeal carcinoma relapsed (5)(6)(7)(8). In our previous report from this cohort study, the hazard ratios associated seropositivity of anti -EBV viral capsid antigen immunoglobulin A and anti -EBV DNase were higher for the nasopharyngeal carcinoma developed <5 years than that developed z5 years after recruitment (13).…”
Section: Discussionmentioning
confidence: 61%
“…Malignancies linked to EBV infection include nasopharyngeal carcinoma, and a variety of methods have been used to detect antibodies against EBV antigens (anti-EBV) in patients with the disease (2,4). Numerous studies have shown diagnostic and prognostic utility of anti-EBV for nasopharyngeal carcinoma (5)(6)(7)(8). Anti-EBVs are found frequently in sera from nasopharyngeal carcinoma patients, and they may be used as a diagnostic tool (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The high titres of IgA antibodies to EA and VCA which are associated with NPC (Henle & Henle, 1976;Zeng, 1985) and the fact that such titres tend to reflect tumour load (Henle et al, 1977) would imply that the tumour itself is the source of these lytic cycle antigens. Indeed some NPC biopsies appear to express transcripts usually associated with entry of cells into the productive cycle Tugwood et al, 1987) and the passage of NPC cells in nude mice in some cases leads to full virus replication in a small proportion of the cells (Trumper et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…A 0.1-unit sample of DNase from crude homogenates of EBV-superinfected Raji cells in a total volume of 5Ml was incubated with 5 ,Ml of serum at room temperature for 20 min. The activity of EBV DNase was then determined as described (17).…”
Section: Methodsmentioning
confidence: 99%